2007
DOI: 10.3892/ijo.31.1.181
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation markers of surfactant proteins in lung cancer

Abstract: Abstract. Surfactant proteins play important roles in lung surfactant function and innate immunity. The DNA methylation state of 11 CpG sites of surfactant protein (SP)-A1, -B, -C, and -D was determined using universal bead arrays. A total of 90 cancerous and non-cancerous tissues from 23 patients with adenocarcinoma and 22 with squamous cell carcinoma were studied. These were divided into a training set and a testing set. The results indicate that DNA methylation profiling of these CpGs is associated with lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The genetic abnormalities in SP-D are associated with lung cancer pathogenesis. 13,14 Reduced SP-D expression in BAL fluid has relevance to subsequent lung cancer risk. 15 The level of SP-D in BAL fluid of patients with idiopathic pulmonary fibrosis (IPF) is decreased 31 and the incidence of lung cancer is increased in patients with IPF.…”
Section: Structures Of N-glycans Of Segfrmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic abnormalities in SP-D are associated with lung cancer pathogenesis. 13,14 Reduced SP-D expression in BAL fluid has relevance to subsequent lung cancer risk. 15 The level of SP-D in BAL fluid of patients with idiopathic pulmonary fibrosis (IPF) is decreased 31 and the incidence of lung cancer is increased in patients with IPF.…”
Section: Structures Of N-glycans Of Segfrmentioning
confidence: 99%
“…The genetic abnormalities in SP-D were associated with lung cancer pathogenesis. 13,14 Reduced SP-D expression in bronchoalveolar lavage (BAL) fluid was linked to subsequent lung cancer risk. 15 Although these studies suggested that SP-D suppressed lung cancer progression, the particular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CpG methylation density is very important due to a fact that low-density CpG methylation would merely repress a weak promoter, while high-density methylation is required for inhibition of a strong promoter (Bird, 1992). Global hypomethylation (Esteller and Herman, 2002) and regional promoter CGIs hypomethylation (Chilukamarri et al, 2007;Lin et al, 2007b;Kim et al, 2008) may activate proto-oncogenes, loss gene imprinting, and reactivate transposable elements. Nevertheless, hypermethylated CGIs may suppress the expression of genes that contribute to tumor suppression, chromatin condensation, and DNA repair (Baylin, 2005).…”
Section: Hypermethylation and Hypomethylation In Lung Cancermentioning
confidence: 99%
“…CpG sites (or islands) are short stretches of DNA with a high cytosine and guanine content (i.e., CG content), with a phosphodiester bond connecting the two residues. Significant differences in the methylation status of two CpG sites of the SFTPA1 gene in lung cancer tissue compared to adjacent non-cancerous (NC) lung tissue have already been reported by us (19). These observations pointed to the possibility that SFTPA1 is a potential biomarker that could be used for diagnosis and treatment of lung cancer (8).…”
Section: Introductionmentioning
confidence: 58%
“…We have previously shown alterations in the DNA methylation profile of genes that encode innate immunity molecules, the surfactant proteins in lung cancer (19). We concluded that methylation/demethylation of CpG sites of the SFTPA1 and SP-D promoters results in altered gene expression and this in turn may contribute to the development of lung inflammatory disease and lung cancer (19). …”
Section: Introductionmentioning
confidence: 99%